2014
DOI: 10.1096/fj.13-247783
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein 1 is a key terminal mediator of inflammation‐induced preterm labor in mice

Abstract: Activation of uterine inflammatory pathways leads to preterm labor (PTL), associated with high rates of neonatal mortality and morbidity. The transcription factors nuclear factor κB (NFκB) and activator protein 1 (AP‐1) regulate key proinflammatory and procontractile genes involved in normal labor and PTL. Here we show that (NFκB) activation normally occurs in the mouse myometrium at gestation day E18, prior to labor, whereas AP‐1 and JNK activation occurs at labor onset. Where labor was induced using the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 56 publications
8
76
1
Order By: Relevance
“…This is consistent with our recent findings showing that murine PTL induced by intrauterine injection of LPS serotype O111:B4 is characterized by AP-1 activation and does not require NF-kB activation. 9 Our data, therefore, provide further evidence that AP-1 activation is a critical regulator of the terminal pathways or labor onset. However, inflammatory transcription factor activation varied greatly between LPS-serotype treatment, as did downstream activation of associated inflammatory and contraction genes and proteins.…”
Section: Lps Serotypes Differentially Activate Uterine Inflammatory Psupporting
confidence: 62%
See 2 more Smart Citations
“…This is consistent with our recent findings showing that murine PTL induced by intrauterine injection of LPS serotype O111:B4 is characterized by AP-1 activation and does not require NF-kB activation. 9 Our data, therefore, provide further evidence that AP-1 activation is a critical regulator of the terminal pathways or labor onset. However, inflammatory transcription factor activation varied greatly between LPS-serotype treatment, as did downstream activation of associated inflammatory and contraction genes and proteins.…”
Section: Lps Serotypes Differentially Activate Uterine Inflammatory Psupporting
confidence: 62%
“…Animals were anesthetized by isoflurane, and a laparotomy was performed as previously described. 9,30,31 Briefly, both uterine horns were exteriorized and the number of live fetuses per horn was recorded. An intrauterine injection of 20 mg [25 mL total volume in phosphate-buffered saline (PBS)] of either E. coli LPS serotype O111:B4, O55:B5, O127:B8, or O128:B12 (Sigma Aldrich, Gillingham, UK) or sterile PBS was injected into the upper right uterine horn between the first and second sacs.…”
Section: Murine Model Of Inflammation-induced Ptlmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising then to see that SB202190 was able to suppress secretion of these inflammatory cytokines and mediators. Shoji et al previously reported involvement of the MAPK pathway in the production of proinflammatory cytokines in the choriodecidua (55)(56)(57). What was unexpected was that BAY 11-7082, an NF-κB inhibitor, did not have a significant effect on the secretion of these cytokines in results, together with our cell viability assays, served as the basis for using 10 mM as the highest concentration in the in vitro experiments here.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 55%
“…Moreover, a causal role of JNK/AP-1 was recently described wherein AP-1 activation alone was sufficient to induce labor and inhibition of JNK was sufficient to delay LPS-induced PTB (37). Correspondingly, SAPK and their target c-jun/c-fos (AP-1) have been shown to be activated in human uterine cervix at term and after delivery, suggesting a concomitant function for AP-1 in cervical ripening (57).…”
Section: Discussionmentioning
confidence: 99%